Capitalism, inequality and labour in India - Breman, Jan (New Delhi Cambridge University Press, 2019)
Jan Breman takes dispossession as his central theme in this ambitious analysis of labour bondage in India's changing political economy from 1962 to 2017. When, in a remote past, tribal and low-caste communities were attached to landowning households, their lack of freedom was framed as subsistence-oriented dependency. Breman argues that with colonial rule came the intrusion of capitalism into India's agrarian economy, leading to a decline in the idea of patronage in the relationship between bonded labour and landowner.